The Effect of Student Participation in Student Activity Units on Learning Achievement - Fatimatuz Zuhro; Waris (BIO-CONS : Jurnal Biologi dan Konservasi, 2022)
This achievement study aims to determine the effect of student participation in the Student Activity Unit (SAU) on student. This study used the Independent-Sample T-Test analysis, which is the analysis used to compare two averages or two groups that are not related and calculated using the SPSS program. The sample in this study was taken from active and inactive students in SAU activities with a total of 40 students. The results showed that the activeness and inactivity of students in SAU activities had no effect on students' Grade Point Avarage (GPA) scores.